2019
DOI: 10.2298/pif1901053p
|View full text |Cite
|
Sign up to set email alerts
|

The effects of casing soil treatment with bacillus subtilis Ch-13 biofungicide on green mould control and mushroom yield

Abstract: The impact of a biofungicide based on Bacillus subtilis Ch-13 on mushroom yield and efficacy in suppression of Trichoderma aggressivum f. europaeum T77 from Serbia was estimated in comparision with a similar microbial fungicide, Bacillus velezensis QST713, and the chemical fungicide prochloraz manganese. The biofungicide B. velezensis QST713 is registered for treatments of mushrooms and other crops in many countries but it is not currently available on the Serbian market. The tested B. subtilis Ch-13 fungicide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 7 publications
5
20
1
Order By: Relevance
“…Many mutualistic bacteria create mushroom substrate benefits to fungal mycelia and influences the fruitbody yield and BE of mushrooms. In a previous study Bacillus subtilis promoted the mushroom yield when applied in lower concentrations [37]. Similarly an enhancement of fruiting body yield in Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 78%
“…Many mutualistic bacteria create mushroom substrate benefits to fungal mycelia and influences the fruitbody yield and BE of mushrooms. In a previous study Bacillus subtilis promoted the mushroom yield when applied in lower concentrations [37]. Similarly an enhancement of fruiting body yield in Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 78%
“…However, Frey-Klett et al (2011) reported that mushroom yield might vary depending on bacterial isolate present in the same medium in casing soil. Potočnik et al (2019) reported that commercial biological preparation B. subtilis Ch-13 was more effective than B. velezensis QST713 against T. aggressivum f. europaeum in casing soil aplications. In this study, commercial biological preparations (A. quisqualis Ag1 and B. subtilis QST 713), bacterial isolates (S. maltophilia and P. rhodesiae) caused the highest yield increases in the treated plots.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (2008) reported that Bacillus species might show antagonistic activity on green mold, while they might also show the same effect on mycelial growth of mushroom species in vitro. In an in vivo study, Potočnik et al (2019) reported that Bacillus velezensis QST713 could adversely affect mushroom yield at high application concentrations. Mohammad and Sabaa (2015) reported that in addition to Bacillus species, Pseudomonas bacteria (e.g., P. putida, P. fluorescens, and P. aeruginosa) present in casing soil had different effects on A. bisporus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, commercial biofungicides such as Serenade ® WP (Bayern, Germany), based on Bacillus velezensis QST713, and Ekstrasol F SC (BioGenesis d.o.o., Belgrade, Serbia), based on Bacillus subtilis Ch-13 1, have been noted effective to control green mold disease when T. aggressivum f. europaeum T77 was artificially inoculated in mushroom plots, showing a biological treatment comparable or even better than those plots treated with prochloraz-Mn [ 120 ]. Although mechanisms involving biocontrol of green mold from biofungicides have been barely described, according to Pandin et al [ 121 , 122 ], the mechanisms acting in the antagonism of T. aggressivum by B. velezensis QST713 may be a combination of (i) competence in the environmental niche through the formation of competitive biofilm to exclude T. aggressivum , (ii) production and secretion of compounds with antifungal activity against the parasite, and (iii) release of signaling molecules, such as volatile organic compounds (VOCs) or the quorum-sensing-controlled processes, which can lead to defense response in A. bisporus or reduce parasite activity.…”
Section: Green Mold ( Trichoderma Spp)mentioning
confidence: 99%